DIFFERENTIATING THE DIMENSIONS OF THE SMART CITY CONCEPT IN METROPOLITAN AREAS - Gorzeń-Mitka, Iwona (Management and Administration Journal, 2024)
The aim of this study is to assess the differentiation of the dimensions of the smart city concept in metropolitan areas on the example of the cities of the Poznan metropolitan area. The analysis covered six basic areas of the smart city concept: smart economy, smart governance, smart mobility, smart environment and smart living. The assessment was carried out using the multi-criteria TOPSIS decision-making method. A total of 31 indicators relating to this concept and identified in the scientific literature were selected as comparative criteria. The analysis covered 14 cities. As a result, seven original rankings were prepared - six presenting an assessment of the cities’ activities in individual smart city areas and a collective ranking indicating the position of individual cities in their efforts to build smart cities against the entire group. These rankings may provide indications for improving the programming of their development by decision-makers of cities located in metropolitan areas in the highlighted areas. By comparing the positions of individual units, it was possible to indicate which of them and in which area have the highest achievements and which smart city issues require a more careful look by decision-makers. The results of the study made it possible to indicate the directions of development of activities that are implemented in individual units against the background of the whole group.